The Shariah Status of DNA Test Evidence in Hudud,Qisas, and Ta'zir - Dr. Fareed Ud Din Tariq, (Al-Qanṭara, 2023)
In Islamic law (Shari’ah), testimony and evidence in matters such as Hudood (prescribed punishments), Qisas (retribution), and Ta’zir (discretionary punishments) are based on firm and reliable principles. Scholars have diverse opinions regarding the use of modern scientific tools like DNA testing. To understand its Shari’ah status, the following points can be considered.Most scholars accept DNA testing as “corroborative evidence.” This means it can be used to support a case with additional evidence but cannot be entirely relied upon. In certain cases where DNA testing provides conclusive proof, scholars debate whether it can be admissible for Hudood or Qisas.In cases of adultery, the Qur’an stipulates the requirement of four eyewitnesses. Therefore, DNA testing alone is not considered sufficient to establish Hadd (punishment) because it does not meet the Shari’ah requirement of witnesses. However, DNA evidence can be used as a supportive means for imposing discretionary punishments (Ta’zir) if other evidence is present.In Qisas cases, such as murder, DNA testing can help identify the perpetrator. However, under Shari’ah principles, two eyewitnesses or a confession are required for Qisas. DNA evidence can serve as corroborative evidence.In Ta’zir cases, the judge (Qadi) has broader authority. DNA testing is generally admissible in discretionary cases, as its use depends on the judge’s Ijtihad (discretionary reasoning) and adherence to general Shari’ah principles while employing modern technology.Certainty is essential for imposing punishments in Shari’ah, and any doubt can nullify them (“Hudood are suspended in the presence of doubt”). Considering the limitations of DNA testing and the possibility of errors, it cannot be regarded as absolute evidence. Expert testimony is also necessary to validate DNA results and confirm their accuracy.Some contemporary scholars and Fiqh councils, such as the Islamic Fiqh Academy, have permitted the use of modern science and technology under specific conditions, particularly in Ta’zir and sometimes in Qisas cases. However, most scholars adopt a cautious approach in Hudood cases and consider DNA only as supplementary evidence.DNA testing is a significant tool of modern science and can be recognized as corroborative evidence in Shari’ah, especially in Ta’zir and Qisas cases. However, its use in Hudood cases is limited because the Qur’an and Sunnah have explicitly defined the requirements for testimony in such matters. Scholars approach this issue through Ijtihad, considering the circumstances, the objectives of Shari’ah, and scientific advancements.